The Design and Implementation of fund management Information System at Nida'ul Fitrah Surabaya foundation - Said, Reza; Sudarmaningtyas, Pantjawati; Mastan, Ignatius Adrian (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Nida'ul Fithrah Foundation asÂ known as (YNF) Surabaya operate to help and facilitate the muslims on the operational YNF recieved handsout sincerely from the donors for operational,facilities, and dakwah costs.based on the survey,averagely thereâ€™s 388 whose miss the payment from 1850 donors. The 2015 cash expenditure not suitable with the foundationÂ policy.for dakwah program cost 14% of 40%,social 83% of 30%,education 5% of 30%.YNF has not done yet the foundation rules according to goverment policy wihich is fund and programs tranparation,and the foundation ownners has not recieved the report of fund and programs that has been finished.The solution is to make fund management information system for YNF using System Development Life Cycle(SDLC) metode,with 4 stages: system Requirements Analysis, Design, Implementation and Testing, and the theory ofÂ PSAK45 by the Indonesian Institute of Accountants(IAI).Based on the test result, the application able to solved the problem,which;activity information and YNF fund recieved by donors,donors get SMS warning message,director gets fund information for the expendeture of the programs so it fit with the foundation policy,the fund flow report recieved by director and foundation owner.the testing result recieve 99,5% point which mean in the range â€œvery satisfiedâ€ that had been measured this application works excellently.